(untitled) - Vietnam Academy of Social Sciences (Ha Noi, 2011)
Poverty reduction poses special challenges in those rural districts of Vietnam that are isolated or face resource scarcity and environmental degradation, and in the slums and squatter settlements of the major cities which are the destination for an increasing number of poor rural migrants. Vietnam's recent market liberalization is not sufficient to reduce poverty in these disadvantaged areas. Distinct, locally appropriate policies and innovative projects are needed.
Keywords: Poverty,Poor,Nghèo; Government policy,Chính sách nhà nước; Vietnam,Vietnam,Việt Nam